2022
DOI: 10.21776/ub.jam.2022.020.01.17
|View full text |Cite
|
Sign up to set email alerts
|

Tik Tok as a Promotional Media to Influence Consumer Purchase Decisions

Abstract: The main purpose of this study is to analyze Tik Tok media as the main consideration in purchasing decisions for culinary products and Tik Tok as a medium for promoting culinary products to purchase decisions. This research was conducted in Denpasar City with a sample of 120 respondents. The data was collected using Google Forms. Data were analyzed qualitative and quantitative using a Likert scale. Inferential statistical analysis was used to draw inference from the sample to the population and hypothesis test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…This research examines the influence of social media marketing TikTok on students' purchasing decisions for Jiniso products. The research results show that using TikTok in marketing can have a positive impact on purchasing decisions (Martini et al 2022).…”
Section: Role Of Tiktok In Digital Marketingmentioning
confidence: 93%
“…This research examines the influence of social media marketing TikTok on students' purchasing decisions for Jiniso products. The research results show that using TikTok in marketing can have a positive impact on purchasing decisions (Martini et al 2022).…”
Section: Role Of Tiktok In Digital Marketingmentioning
confidence: 93%
“…The expected effort invested by the tourist when using TikTok has a positive influence on the tourist's decision about the travel destination, and the authors reached these results (Zhou et al, 2023;Wang et al, 2022, Du et al, 2022Zhou et al, 2015). Authors who examined the social influence of TikTok on tourists' travel decisions concluded that there was a significant positive impact (Zhou et al, 2023;Zainal et al, 2023;Martini et al, 2022;Li, 2021). Compared to other social networks, TikTok's terms of use make it easier for potential travelers to search for travel.…”
Section: Source: Authormentioning
confidence: 96%
“…Previous studies have focused on the TikTok as a promotional media to influence consumer purchase decision (Martini et al, 2022). This research has been con- Other previous studies have only focused on social media marketing and its effects on TikTok users (Azpeitia, 2021).…”
Section: Problem Statementmentioning
confidence: 99%